2023
DOI: 10.3389/fphar.2023.1067422
|View full text |Cite
|
Sign up to set email alerts
|

Functional enhancement strategies to potentiate the therapeutic properties of mesenchymal stromal cells for respiratory diseases

Abstract: Respiratory diseases remain a major health concern worldwide because they subject patients to considerable financial and psychosocial burdens and result in a high rate of morbidity and mortality. Although significant progress has been made in understanding the underlying pathologic mechanisms of severe respiratory diseases, most therapies are supportive, aiming to mitigate symptoms and slow down their progressive course but cannot improve lung function or reverse tissue remodeling. Mesenchymal stromal cells (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 263 publications
0
3
0
Order By: Relevance
“…In previous studies, the homing feature of MSCs has been observed to predominantly target the site of injury in cases of ischemia, hypoxia, and injury. 30 The results of our study indicatethat transplanted ADSC may be play a role in repairing kidney damage in situ after they have been injected into kidney tissues.…”
Section: Discussionmentioning
confidence: 63%
“…In previous studies, the homing feature of MSCs has been observed to predominantly target the site of injury in cases of ischemia, hypoxia, and injury. 30 The results of our study indicatethat transplanted ADSC may be play a role in repairing kidney damage in situ after they have been injected into kidney tissues.…”
Section: Discussionmentioning
confidence: 63%
“…In addition to confirming cell homing is not necessary for imparting therapeutic effects [25], this finding strongly supported a paracrine MoA. Multiple studies have also convincingly demonstrated that the immunomodulatory effect of MSCs is communicated via MSC and recipient-secreted cytokines and relies on the local microenvironment [19,[26][27][28][29], as some of the observed effects depend on a pre-treatment of MSCs with inflammatory cytokines [27,28,30]. More recent findings indicate that the cytokine-mediated effects are only one part of the equation, as MSC-derived microparticles (including exosomes), apoptotic, metabolically inactivated, or even fragmented MSCs and MSC-membranes have immunomodulatory potential [31][32][33][34][35].…”
Section: Mscs Are Not Required For Therapeutic Effect In Sepsis/alimentioning
confidence: 64%
“…The requirement for licensing or activation for MSCs to mediate their immunomodulatory or cytoprotective effects is now better understood [28]. In particular, simulation with IFN-γ, TNF-α, IL-1β or combinations of these cytokines enhances MSC therapeutic efficacy in vitro and in vivo [14,94,95].…”
Section: Licensing Of Mscs Alters Ev Mir Content and Therapeutic Acti...mentioning
confidence: 99%
“…Recent research has shed light on the paracrine effect and MSC membranes as key mechanisms responsible for their therapeutic properties . Exposure of MSCs to inflammatory factors could upregulate immunomodulatory mediators, adhesion molecules, and chemokines and promote inhibition of NK cell activation and immunosuppressive effects on T lymphocytes . In previous work, we successfully fabricated large efficacy-potentiated exosome-mimicking nanovesicles (L-Meseome) by using membranes and secretomes from efficacy-potentiated MSCs induced by Tumor necrosis factor α (TNFα) and Interferon γ (INFγ), which showed that L-Meseomes had many proteins related to tissue regeneration, including angiogenic proteins fibroblast growth factor 2 (FGF2), vascular endothelial growth factor A (VEGFA), and antioxidant-related proteins superoxide dismutase 2 (SOD2).…”
Section: Introductionmentioning
confidence: 99%
“…13 Exposure of MSCs to inflammatory factors could upregulate immunomodulatory mediators, adhesion molecules, and chemokines and promote inhibition of NK cell activation and immunosuppressive effects on T lymphocytes. 14 In previous work, we successfully fabricated large efficacy-potentiated exosome-mimicking nanovesicles (L-Meseome) by using membranes and secretomes from efficacy-potentiated MSCs induced by Tumor necrosis factor α (TNFα) and Interferon γ (INFγ), which showed that L-Meseomes had many proteins related to tissue regeneration, including angiogenic proteins fibroblast growth factor 2 (FGF2), vascular endothelial growth factor A (VEGFA), and antioxidant-related proteins superoxide dismutase 2 (SOD2). Some inhibition of inflammation-related proteins, such as tumor necrosis factor alpha-induced protein 6 (TSG6), indoleamine 2,3-dioxygenase (IDO), can inhibit inflammation, inhibit apoptosis, and promote angiogenesis, and had a certain therapeutic effect on the tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%